Taxonomies of User Experience (UX) evaluation methods - Rajeshkumar S.; Omar R.; Mahmud M. (2023)
User Experiences (UX) and Usability are tightly coupled. They are yardsticks for successful interaction designs. Various methods are available to evaluate UX and usability respectively. Many arguments are presented in order to either distinguish or identify common grounds between the two. These evaluation methods are used in various different contexts and environments, and they fall into different types of taxonomy. Several UX and usability evaluation methods were reviewed and summarized in this paper. The result of analysis and observation indicates that there are correlations and disassociations between UX and Usability. 2013 IEEE.